FAKTOR – FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA TAHUN 2012 - 2016 - Satrio Agung Nugroho, 14.05.52.0176; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of underwriter reputation, auditor reputation, current ratio, firm age, and return on asset on underpricing. This research is conducted in Bursa Efek Indonesia (BEI), a company that has go-public. The population of this study is a company that conducted an IPO in 2012 until the year 2016 in Indonesia Stock Exchange. Sampling method using purposive sampling with research period year 2012 until 2016 and obtained by 71 company. Underpricing as measured by initial return is the dependent variable in this study. While the independent variables in this study is the current ratio, company age and return on assets. The results showed that firm age and return on assets significantly negatively impacted underpricing. While current ratio has no significant effect on underpricing.Keyword: Underpricing, current ratio, firm age, and return on asset